Improving e-learning websites: the role of menu depth and metacognitive support - Beege, Maik; Scherer, Demian; Weiß, Elena (Frontiers in Education, 2023)
Results from experimental research in instructional psychology imply that a deep menu structure of a e-learning website may provide useful segmentation. However, menu depth also increases the need for navigation and thus, might have impairing effects on learning. Furthermore, instructional support can be provided by including a checklist, to ensure that learners reflect on their study progress. The study aimed at investigating which menu structure is beneficial for e-learning websites and whether a checklist could compensate the negative effects of an unfavorable menu structure. Therefore, in an online experiment, we let 101 students learn facts about rocks from an e-learning website with either a deep or a flat menu structure. We further manipulated whether metacognitive support through a checklist was provided or not. Learning outcomes, cognitive load, metacognitive factors as well as learning time were measured. Results show no main effects of the menu depth or the presence of a checklist on retention and transfer performance. Learning achievements in percent for retention were 37.31 (deep menu/checklist), 31.10 (deep menu/no checklist), 36.07 (flat menu/checklist), 38.13 (flat menu, no checklist) and for transfer were 35.19 (deep menu/checklist), 34.40 (deep menu/no checklist), 37.78 (flat menu/checklist), 33.23 (flat menu, no checklist). Yet, there are hints that the deeper menu structure had a negative effect on learning processes: The deep menu structure led to an enhanced extraneous cognitive load (ECL) and reduced learning efficiency. However, providing a checklist had beneficial effects mainly when learning with a deep menu structure but not overall. Unexpectedly, the presence of the checklist did not influence metacognitive measures. Our study suggests that possible costs of a deep menu structure should be considered when designing instructional checklists. However, the study also provides a way in which these costs can be compensated, which is by using a checklist. Implications for instructional research and e-learning are discussed.